2001
DOI: 10.1002/j.2050-0416.2001.tb00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Size Characterization of Barley Starch Granules Determined by Electron and Optical Microscopy, Low Angle Laser Light Scattering and Gravitational Field-Flow Fractionation

Abstract: Several methods were used for the characterization of starch granules isolated from barley kernels. A procedure based on a combination of alkaline digestion, toluene treatment and filtration over sieves with pore diameters of 70 and 40 μm was used for isolation and purification of starch granules from kernels. The released starch granules were characterized by various methods: scanning electron microscopy (SEM), image analysis of optical microscopy data (IAOM), low angle laser light scattering (LALLS), and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 14 publications
0
33
0
1
Order By: Relevance
“…However, SEM is frequently used to determine granule size. It also provides a more detailed perspective on granule surface characteristics and granule morphology (Chmelik 2001). Various studies, using x-ray photoelectron spectroscopy and SEM have revealed that the starch granule surface is predominantly (90% to 95%) carbohydrate in nature (Oostergetal and van Bruggen 1993;Calvert 1997).…”
Section: Starch Morphologymentioning
confidence: 99%
“…However, SEM is frequently used to determine granule size. It also provides a more detailed perspective on granule surface characteristics and granule morphology (Chmelik 2001). Various studies, using x-ray photoelectron spectroscopy and SEM have revealed that the starch granule surface is predominantly (90% to 95%) carbohydrate in nature (Oostergetal and van Bruggen 1993;Calvert 1997).…”
Section: Starch Morphologymentioning
confidence: 99%
“…GFFF has been employed for the separation, characterization and micropreparation of a wide variety of biological, inorganic and synthetic particulate materials, such as cells [2][3][4][5], starch granules [6][7][8][9][10][11], silica gel particles [12][13][14], polymer latexes [15], fine coal particles and residues from coal liquefaction [16].…”
Section: Open Accessmentioning
confidence: 99%
“…In the endosperm, starch can be found in two configurations: A-granules with average diameter range of 10-40 mm and B-granules with average diameter range of 1-10 mm with an approximate weight ratio (A:B) of 9:1 and total number ratio (A:B) of 1:9. [2,[49][50][51] The embryo largely contains oil and protein with little starch. [12] Knowing that the starch granule size approximately corresponds to the pore size, [31] we measured the pore surface area-to-volume ratio (S=V p ) of the confining space or, in other words, the pore geometry of the starch granules from the c values given in Table 1.…”
Section: Pore Geometrymentioning
confidence: 99%